Upgrading the global value chain with regime-wide rules of origin. Issue 2 (19th January 2021) - Doan, Thang Ngoc; Le, Ha Thanh
ABSTRACT: Participation in the global value chain (GVC) is defined as the value added contained in exports, looking both backward and forward from a reference nation. This article applies the gravity model to investigate the effects of the regime-wide rules of origin (RoO), including diagonal cumulation, de minimis, and self-certification requirements, on GVC participation with 40, 568 observations covering 61 countries from 2005–2015. Our main finding is that the liberal RoO can help upgrade both types of GVC participation.